Teachers$1 (BSpecial Education Referrals for Younger Children Vary by School Types - Tina L. Fletcher, PhD; Phil H. Kim, MEd
The prevalence of disability diagnoses among young children has risen significantly over recent decades. This growth has prompted inquiries into the identification processes, notably focusing on teachers who are the primary sources of referrals. While some studies have examined child age as a relevant predictor of disability referral, minimal attention has been paid to relative age$1 (Bnamely, if children are younger than their classmates. In this study, we examine whether teachers in the U.S. state of Arkansas refer children differently based on relative classroom age. We do so for traditional public schools versus magnet schools, as each type has been shown to serve different student populations. Results show no significant association between classroom age composition and referral rates in either school type. However, in traditional public schools, a higher proportion of younger children in classrooms correlated with a higher proportion of referrals for younger children, whereas magnet schools showed no such trend. Policy implications are discussed.s